Craniofacial morphology of orthodontic patients with temporomandibular disorders - SAKUDA, Mamoru; TERADA, Yasuo; TANAKA, Eiji; TANNE, Kazuo; SHIBAGUCHI, Tatsuya (Journal of the Japanese Society for the Temporomandibular Joint, 1994)
The purpose of this study was to investigate the association between temporomandibular disorders (TMD) and the craniofacial morphorogy of orthodontic patients. 133 patients with TMD (TMD group) and 162 patients without TMD (control group) were selected as subjects. Each TMD subject presented at least one of such TMD symptoms as TMJ sounds, TMJ pain, muscle tenderness and difficulty of jaw movement. The subjects were divided into nine types of malocclusion by vertical and horizontal occlusal relations. Craniofacial morphology was evaluated by cephalometric analysis, and the values of cephalometric measurements were compared between TMD and control groups. The following results were obtained. (1) In open bite with anterior crossbite or maxillary protrusion, the mandibular plane angle was significantly larger in the TMD group than in the controls. In open bite without any anteroposterior occlusal problems, the gonial angle was significantly larger in the TMD group than in the controls. (2) No significant differences in craniofacial morphology were found in the remaining types of malocclusion. It is suggested that abnormality of craniofacial morphology is pertinent to the occurrence of TMD in certain types of malocclusion, in terms of the influences on mandibular or condylar position.